2015
DOI: 10.3171/2015.5.peds1531
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic corpus callosotomy and hemispherotomy

Abstract: Endoscopic corpus callosotomy and hemispherotomy are surgically feasible procedures associated with minimal blood loss, minimal risk, and excellent visualization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 13 publications
0
53
0
Order By: Relevance
“…While many investigators have suggested that only anterior callosotomy is necessary to achieve clinical benefit, others advocate for a complete callosotomy [87]. One group has recently proposed performing a callosotomy using an endoscopic approach [114]. …”
Section: Disconnection Proceduresmentioning
confidence: 99%
“…While many investigators have suggested that only anterior callosotomy is necessary to achieve clinical benefit, others advocate for a complete callosotomy [87]. One group has recently proposed performing a callosotomy using an endoscopic approach [114]. …”
Section: Disconnection Proceduresmentioning
confidence: 99%
“…In a subsequent cadaveric report, a frontal precoronal craniotomy was used to achieve a total endoscopic callosotomy [4]. In a recent report, Sood, et al used the same precoronal route to successfully perform an endoscopic total callosotomy in four patients [7]. However, even if the above described technique represents a minimally invasive approach of performing a corpus callosotomy, it still necessitates a small craniotomy and a microscopic interhemispheric approach before switching to the endoscopic portion of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…4 We do not understand how the authors claim their originality on this technique when our paper was already published 1 before their own paper (date of acceptance of our paper: January 4, 2015, vs date of acceptance of Sood et al's paper: May 11, 2015). Even the PubMed publication shows our paper to have been published April 2015, while Sood and colleagues' paper was published September 2015.…”
Section: Margaret Kaminska MDmentioning
confidence: 91%
“…2 We wonder if any of those patients who went through tapering off of oral baclofen encountered any significant clinical problems. In our practice, we have encountered a case of severe spasticity due to multiple sclerosis, 4 that was minimally responsive to baclofen (60 mg 3 times daily) and tizanidine (4 mg 3 times daily), in which completely tapering off oral baclofen was deemed unfeasible. The patient had previously experienced severe spinal headache following lumbar puncture and therefore she firmly refused an ITB trial.…”
Section: Responsementioning
confidence: 99%
See 1 more Smart Citation